Females of the genus Podmosta (Plecoptera: Nemouridae): comparison of terminalia and a new female record in Baltic Amber - Chen, Zhi-Teng (Zootaxa, 2018)
Based on a specimen preserved in Baltic amber from Lithuania, a new fossil female of the nemourid genus Podmosta Ricker, 1952 is described, illustrated and compared to other described species of the genus. The new female specimen is distinguished from other Podmosta females by the “rabbit-shaped” sclerite on sternum 8.